CYP1B1 knockout enhanced IFN-γ production is required but not sufficient for protection of cigarette smoke-exposed mice against lethal influenza virus infection - Wu, Wenxin; Alexander, Jeremy S.; Booth, J. Leland; Chlebicz, Magdalena; Miller, Craig A.; Xu, Chao; Kovats, Susan; Metcalf, Jordan P. (Frontiers in Immunology, 2025)
BackgroundCigarette smoke (CS) exposure increases the frequency and severity of respiratory influenza A virus (IAV) infections in humans and increases mortality in mice. There is evidence that Cytochrome P450 family 1 subfamily B member 1 (CYP1B1) enhances lung injury during hyperoxic exposure in animal models. We used an in-vivo mouse model to assess the hypothesis that CYP1B1 modifies innate immune responses to CS and alters survival during IAV infection.MethodsWe measured CYP1B1 induction in bronchial epithelial cells in smokers and nonsmokers obtained by bronchoscopy by whole transcriptome analysis. To determine whether CYP1B1 knockout (CYP KO) improves mortality and reduces lung injury in CS-exposed mice, we compared the survival rates, host immune responses, and lung-to-body weight ratio of CYP KO mice with the wild-type (WT) mice following challenge with IAV with or without CS exposure.ResultsCYP1B1 is one of the most highly upregulated genes in human lung epithelia derived from cigarette smokers. In CS-exposed mice, CYP1B1 knockout (CYP KO) significantly increased survival during IAV infection. In both nonsmoking (NS) and CS mice, CYP KO significantly enhanced IAV-induced increases in total immune cell numbers in bronchoalveolar lavage fluid (BALF) without causing additional lung injury. CYP KO caused a more rapid IFN-γ response to IAV infection in lungs from both NS- and CS-exposed mice. Specifically, we found that IFN-γ was significantly increased in BALF and in the lung at day 5 post-infection (p.i.) in these mice. Flow cytometry showed that innate lymphocytes produced early IFN-γ in the lungs of KO mice. We confirmed the importance of IFN-γ for CYP KO survival by adding IFN-γ antibody to IAV-infected CYP KO mice. IFN-γ antibody treatment of CS-exposed CYP KO mice completely abolished the improved survival rate seen in KO mice without IFN-γ antibody treatment. However, IFN-γ administration to CS-exposed WT mice did not increase survival rates as seen in CS-exposed CYP KO mice after IAV infection.ConclusionsOur results demonstrate that CYP KO in mice protects against CS-enhanced susceptibility of smokers during influenza infection. IFN-γ is required but not sufficient for the protection of CS-exposed CYP KO mice against lethal IAV infection.